Upaya Meningkatkan Kemampuan Bahasa Anak Usia 5-6 Tahun Melalui Media Digital Dongeng - Andri Hardiyana; Nur Yati (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2021)
Language ability in early childhood is a vital ability needed to support the development of life. This is so that children are able to develop optimally according to their developmental age. The purpose of this study was to describe and improve the language skills of children aged 5-6 years through digital media fairy tales at PAUD Bina Bhakti Wanita Wanacala Cirebon City. The method used in this research is classroom action research. The place and time of the research was carried out at PAUD Bhina Bakti Wanita Wanacala Cirebon City and carried out in October-December 2020. Data collection techniques used in this study were observation, documentation study, and interviews. The subjects of the study were children in group B of the Bina Bhakti Wanita Wanacala Playgroup, Cirebon City, which amounted to 20 children. The results of this study indicate that the acquisition of language skills of children aged 5-6 years with details of each Pre-cycle 4.5%, Cycle I 69.5% and Cycle II 89.3%. This shows that there is an increase in aspects of children's language skills through digital media fairy tales with an achievement of 89.3%.